Bias Disclosures, Complicated Mice and a Digital Diss (The Scientific World Journal)
Nature reports first this week on a controversial new study about the lack of author disclosure in journals of possible conflicts of interest that may or may not color research results. In Science, the mouse genome sequence's problematic progress leads the news.